Rekayasa Lingkungan Dan Valuasi Ekonomi Objek Wisata Air Terjun Kandua Raya Desa Kedang Ipil, Kecamatan Kota Bangun, Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Ansahar, Ansahar; Sinaga, Yunita (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2018)
Abstract:The establishment of the village of Kedang Ipil as tourist village could not be separated from the presence of natural attractions in the form of Kandua Raya Waterfall that often become a destination vacation or recreation for the surrounding communities and region in particular communities of East kalimantan. This research is useful for manager or as reference for related party interested in the preparation of Kandua Raya tourism development. Data obtained either the primary data, secondary data and ancillary data are analyzed in a descriptive, quantitative and qualitative. The strategy of the development of nature tourism is in the SWOT analysis to maximize the strength and opportunities of development activities towards local communities, yet simultaneously also can minimize weakness and threats that are contained in it. Knowledge of the economic value ofÂ natural resources and the environment is important, both for the managers, the public, as well as the related agencies. The support of the relevant agencies and the positive attitude of the public is indispensable. Moreover, the road to accessibility to the site is still difficult. Need to repair the road Infrastructure. However, institutions involved and the determination of responsibility does not match the task.Keywords: Environment, waterfall, tourism